Recreational use of the urban riverscape: What brings people to the river? - Grzyb Tomasz (Moravian Geographical Reports, 2024)
Visiting urban green and blue spaces improves the quality of life in cities as it helps to preserve human-nature bonds. In this context, the role of urban parks and forests has been well-recognised; however, much less is known about the landscapes of inland water bodies. To fill this gap, the study aimed to identify spatiotemporal patterns of recreational activities in the urban riverscape in relation to the visitors’ residential proximity. Also, survey results were combined with spatial and remote sensing data to determine how the spatial characteristics of the riverscape affect its recreational use. The case of Warsaw, Poland, was used. The results indicated that the riverscape serves as a local park for the neighbouring communities, while it is rather a warm-weekend attraction for far-living ones. Visitors concentrate in the city centre, and spread out along the communication paths; however, spatial patterns of the magnitude of particular activities also show interbank differences. Spatial error models of drivers of riverscape recreation revealed (1) the multifaceted role of trees in densely visited areas and (2) the importance of physical availability for contact with the urban river. These findings expand knowledge on the recreational use of urban rivers by exploring its place-related motivations.